Facilitators and barriers to medication self-management for patients with multiple long-term conditions transitioning from hospital to home - Malin Olsen Syversen; Mikas Glatkauskas; Liv Mathiesen; Marianne Lea; Berit Gallefoss Denstad; Karin Svensberg (Exploratory Research in Clinical and Social Pharmacy)
Background: Being a patient with multiple long-term conditions (MLTCs) often entails a need for complex medication treatment, which poses a challenge to medication self-management. Medication self-management during transition of care is often hindered by challenges such as inadequate communication, which increases the risk of medication errors and adverse outcomes. Aim: Identify facilitators and barriers to medication self-management for patients with MLTCs transitioning from hospital to home. Methods: Semi-structured interviews were conducted in patient's homes 1–2 weeks after hospital discharge. Interviews were transcribed and analysed by qualitative deductive content analysis using the Taxonomy of Every Day Self-management Strategies (TEDSS) framework. The data collection continued until enough information power and meaning saturation was reached. Results: Twenty-one patients and three next of kin participated. Numerous facilitators and barriers to medication self-management were identified within all seven TEDSS domains, which varied extensively between individuals. Resource and process strategies were the most frequently discussed domains, while health behaviour and social interaction strategies were less frequently discussed. Key facilitators identified were access to resources that support medication self-management and knowing the medication's purpose. Key barriers included patients perceiving medications as burdensome or not recognising the importance of their medications. Conclusions: This study highlights the complex and wide spectre of facilitators and barriers to medication self-management for patients with MLTCs transitioning from hospital to home. In clinical practice, patients' medication self-management could be supported through a holistic approach adapted to the individual patient's daily life, including improved care coordination and patient empowerment.